Gazdasági szakos hallgatók tanulási motivációjának és személyes kompetenciáinak vizsgálata - Gergely, Éva; Nagy, Richárd (Közép-Európai Közlemények, 2016)
The research deals with revealing studying motivations and personal competences of university students. The sample includes students specialized in certain economic fields at the University of Debrecen. A survey was carried out, the number of the elements of the sample was 121. The students were asked to evaluate certain personal competences in one part of the survey. The evaluation of students relating to willingness for innovation, motivation for managerial function, problem solving capacity, sturdiness, tendentiousness and work schedule were investigated. The willingness for innovation got the lowest value, while commitment and result and target orientation got the highest values. When revealing the studying motivations, influences by the family and friends, the tendentiousness, realizing the would-be financial independence, experiencing university memories and improving moral existence were examined.